If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -7) = 66(x + 1) Reorder the terms: 2(-7 + x) = 66(x + 1) (-7 * 2 + x * 2) = 66(x + 1) (-14 + 2x) = 66(x + 1) Reorder the terms: -14 + 2x = 66(1 + x) -14 + 2x = (1 * 66 + x * 66) -14 + 2x = (66 + 66x) Solving -14 + 2x = 66 + 66x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-66x' to each side of the equation. -14 + 2x + -66x = 66 + 66x + -66x Combine like terms: 2x + -66x = -64x -14 + -64x = 66 + 66x + -66x Combine like terms: 66x + -66x = 0 -14 + -64x = 66 + 0 -14 + -64x = 66 Add '14' to each side of the equation. -14 + 14 + -64x = 66 + 14 Combine like terms: -14 + 14 = 0 0 + -64x = 66 + 14 -64x = 66 + 14 Combine like terms: 66 + 14 = 80 -64x = 80 Divide each side by '-64'. x = -1.25 Simplifying x = -1.25
| 6Q-27+Q^2=0 | | 2x^4-3x^3-7x^2-3x-9=0 | | y-7=3y-4 | | 1/2(2x=2)-1/4(3x-1)=15 | | 4+1+4s+5s+5+S=29 | | x=6y-9cos(5+y) | | 60=x(x-3) | | 105=.5h(10+5) | | 0.75x=3 | | 4y=4y+24 | | (f+9)(x)=f(x)+g(x) | | 9x=2x+4 | | 25/15x-13/10 | | 2x(x-7)=6(x+1) | | tan(pi/x) | | 4/h=12/24 | | 9x^2-48x+96=0 | | 9x^2-64x+96=0 | | -7x-5=5x+7 | | 18-4(3f+5)-f= | | (v^2+35)=(-12v-1) | | x+8+4x+3=243 | | 2.1x-5=-1.9x-5 | | 13/21*1/5*7/26 | | -e^(-x^1/25)=0 | | -3(6-6x)-3=x-4 | | 1-3x+x^3=0 | | -3(6-6x)-3=x | | 18x+8=11x+5 | | y=3-1x | | 2x+15=3x-70 | | 6y+3t= |